Pembuatan Animasi Aset 3D dalam Film Pendek Gugu si Gonggong Ajaib sebagai Media Promosi UMKM Menggunakan Blender 3D - Aqid, Aizudin; indonesia, indonesia (Politeknik Negeri Batam, 2025)
The development of digital technology opens up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to increase their competitiveness through 3D animation-based promotional media. This study aims to design and animate 3D assets in the short film